Food Insecurity and Cardiometabolic Risk Factors in Adolescents - Robson, Shannon M. (Prev Chronic Dis, 2017)
INTRODUCTION: Food insecurity is associated with poor cardiometabolic health in adults. The extent to which this relationship exists in adolescents has yet to be defined. The objective of this study was to examine the relationship between food insecurity and cardiometabolic risk factors in adolescents. METHODS: We evaluated the association between food insecurity and several cardiometabolic risk factors by using data collected from the Youth Risk Behavior Survey at the state and city levels. Logistic regression models adjusted for sex, race/ethnicity, grade, and neighborhood safety were used to determine the association between food insecurity and cardiometabolic risk factors among a weighted sample of 495,509 adolescents. RESULTS: Of the sample studied, 12.8% reported being food insecure. Food-insecure adolescents had more than a twofold increased odds of not eating breakfast on all 7 days (adjusted odds ratio [AOR] = 2.27; 95% confidence interval [CI], 1.61–3.21; P < .001), a 60% increased odds of reporting less than 8 hours per day of sleep (AOR = 1.60; 95% CI, 1.15–2.23; P = .006), a 65% increased odds of reporting current cigarette smoking (AOR = 1.65; 95% CI, 1.16–2.36; P = .006), and a 65 % increased odds of current alcohol consumption (AOR = 1.36; CI, 1.01–1.84; P = .04), compared with food-secure adolescents. CONCLUSION: Among adolescents, in adjusted models, food insecurity was significantly associated with not consuming breakfast daily, getting less than 8 hours of sleep per day, currently smoking, and currently drinking alcohol. Food insecurity in adolescents may serve as an important precursor to poor cardiometabolic health.